Major and trace elemental concentration from sediment core EW0408-87JC and IODP Site 341-U1418 in abyssal-water depth from the Gulf of Alaska, Northeast Pacific - Jianghui Du; Alan C Mix; Brian A Haley; Christina L Belanger; Sharon (PANGAEA, 2022)
Here we report the sediment major and trace element geochemistry at two water depths in the Gulf of Alaska, Northeast Pacific, spanning the last ~50 kyr. These data were used to reconstruct past ocean deoxygenation and regional volcanism. Site EW0408-87JC and co-located IODP Site 341- U1418 are from the abyssal depth (3680 m). Elemental concentration data were collected using ICP-MS and ICP-OES at Oregon State University.